Papillary glioneuronal tumor: a new entity awaiting inclusion in WHO classification - Bhatia Alka; Kumar Yashwant; Radotra BD; Mohindra Sandeep (BMC, 2007)
Abstract Papillary glioneuronal tumor (PGNT) is a recently described lesion of the brain, which is still not included as a separate entity in WHO classification. To date 32 cases of PGNT have been reported in the world literature. We report the 33rd case, a 41-year-old male who presented with pain in the nape of the neck. MRI showed a large, predominantly solid mass involving the cerebral parenchyma of the left temporal and parieto-occipital lobes with extension across the midline. Histologically, it was a mixture of glial and neuronal components. Architecturally, the tumor was notable for its pseudopapillary pattern with hyalinized vessels. PGNT is considered as a low grade neoplasm and surgical excision has been curative in most of the cases. More cases of PGNT need to be reported as they may add further knowledge about its biologic behavior and allow its recognition and classification.